PENGGUNAAN MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA DALAM MATA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SD NEGERI BIBIS, BANTUL, DIY - Fania Nova Emalia; Beny Dwi Lukitoaji (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The ibackground iof ithis istudy iis ithe ilow iacademic iachievement iof istudents, iwhich iis iattributed ito ithe ilack iof iuse iof iinstructional imedia iduring iclassroom ilearning iactivities. iTo iaddress ithis iissue, ithe iresearcher icollaborated iwith ithe iclassroom iteacher iwith ithe iaim iof iimproving ithe ilearning iprocess, iwhich iwas iconsidered iinadequate. iThe ilearning iprocess iutilized iWordwall ias ia ilearning imedium, iwhich iwas iexpected ito ienhance ithe iacademic iperformance iof iGrade iIVB istudents iat iSD iNegeri iBibis iin ithe isubject iof iPancasila iEducation. iThis istudy iis ia iClassroom iAction iResearch i(CAR). iThe isubjects iof ithe iresearch iwere i25 istudents ifrom iGrade iIVB iat iSD iNegeri iBibis. iData icollection iwas iconducted iusing itests iin ithe iform iof ipre-tests iand ipost-tests, iobservation isheets, iinterviews, iand idocumentation. iThe idata ianalysis ifor istudent iacademic iachievement iemployed idescriptive iqualitative ianalysis ibased ion iquantitative idata, iafter icalculating iall iassessment icomponents iand idetermining ithe iaverage iscores. iThe iresults iof ithe ianalysis ishowed ian iimprovement iin ithe iacademic iachievement iof iGrade iIVB istudents iat iSD iNegeri iBibis iBantul, iYogyakarta iSpecial iRegion i(DIY), iin ithe isubject iof iPancasila iEducation. iIn iCycle iI, ithe ipre-test iaverage iscore iwas i56, iwith ia imastery ilevel iof i12%. iAfter ione ilearning isession iin iCycle iI, ithe ipost-test iaverage iscore iincreased ito i69.60, iwith ia imastery ilevel iof i68%. iIn iCycle iII, ithe ipre-test iaverage iscore iwas i69, iwith ia imastery ilevel iof i72%. iAfter ione isession iin iCycle iII, ithe ipost- test iaverage iscore iincreased ito i82, iwith ia imastery ilevel iof i95%. iThese iresults iindicate ithat iin iCycle iII, istudents' iacademic iachievement iimproved iin ithe isubject iof iPancasila iEducation iand imet ithe iMinimum iMastery iCriteria i(KKM) istandard iof ia iscore i≥ i70, iachieving i80% iby ithe iend iof ithe icycle.